Cyclic tensile loading regulates human mesenchymal stem cell differentiation into neuron-like phenotype - Leong, Wen Shing (2013)
Mechanical loading has been utilized as an effective tool to direct mesenchymal stem cells (MSCs) commitment into cell lineages of mesodermal origin. However, the use of this tool to induce transdifferentiation of MSCs into the neural lineage has never been attempted. In this study, we examined the potential of uniaxial cyclic tensile loading in promoting neuronal differentiation of human MSCs (hMSCs) on modified biodegradable poly(ε-caprolactone) (PCL). The stem cell morphology, tissue-specific gene and protein expression, microfilament structure and, subsequently, Rho GTPase activity were analysed after cyclically stretching the cells at a range of amplitudes (0.5%, 2% or 3.5%) and frequencies (0.5, 1 or 1.5 Hz) for 8 h. hMSCs responded to these stimuli and displayed distinctly different microfilament organization. However, only those stretched at 0.5% strain amplitude and 0.5 Hz frequency showed promoted outgrowth of filopodia with significant upregulation of neurogenic genes expression. Positive staining of the neurogenic protein markers Nestin and Tuj1 suggested that the hMSCs had been committed to early neuronal progenitors. In addition, Rac1 but not RhoA was activated at this particular loading parameter. Furthermore, inhibition of Rac1 activity with NSC23766 disrupted the effect of cyclic loading. The results suggest that cyclic tensile loading at low amplitude and frequency is capable of triggering neuron-like differentiation through the regulation of Rho GTPases activity, even in the absence of neurogenic induction medium.